hw_3_solution_2009

hw_3_solution_2009 - Homework #3 Solutions ECE 15a Winter...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon
Homework #3 Solutions ECE 15a Winter 2009 Solution 1: (a). f = (u+v) (uv’ + u’w)’ = (u+v) [ ( u’+v ) ( u+w’) ] = (u+v) (u’+v) (u+w’) = (uv + u’v) (u+w’) = v (u+w’) = uv(w+w’) + (u+u’)vw’ = uvw + uvw’ + uvw’ + u’vw’ = uvw + uvw’ + u’vw’ (b). g = xy’z + (x’+y) (x+z’) = xy’z + x’z’ + xy = xy’z + x’ (y+y’) z’ + xy (z+z’) = xy’z + x’yz’ + x’y’z’ + xyz + xyz’ (c). h =(x+z) (x+y’) (x’+z’) = (xz’+x’z) (x+y’) = xz’x + xz’y’ + x’zx + x’zy’ = xz’ + xz’y’ + 0 + x’y’z = x (y+y’)z’ + xz’y’ + x’y’z = xyz’ + xy’z’ + x’y’z
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Solution 2: (a). f = x’ + y’ = x’ (y+y’) (z+z’) + (x+x’) y’ (z+z’) expanding the above expression and neglecting redundant terms we get, = x’yz + x’y’z + x’yz’ + x’y’z’ + xy’z + xy’z’ (b). g = x’z’ + x’z = x’ (z+z’) = x’ = x’ (y+y’) (z+z’) = x’yz + x’yz’ + x’y’z + x’y’z’ Solution 3:
Background image of page 2
Image of page 3
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 03/02/2009 for the course ECE 15A taught by Professor M during the Winter '08 term at UCSB.

Page1 / 5

hw_3_solution_2009 - Homework #3 Solutions ECE 15a Winter...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online